EKSPLORASI ALASAN UTAMA RESISTENSI TERHADAP QRIS : STUDI KASUS PADA UMKM KECAMATAN KERSANA KABUPATEN BREBES - Citra Karyaniasih, Berlian Widinda; Apriani, Ari (Taksasila Edukasi Insani, 2025)
This study aims to explore in depth the main reasons behind the preferences of Micro, Small, and Medium Enterprises (MSMEs) in Kersana District for the use of physical money and their resistance to the implementation of the Quick Response Code Indonesian Standard (QRIS) digital payment system. This study was motivated by the slow adoption of digital payment technology among MSMEs despite the government's massive push for digital transformation. The research method used is a qualitative approach utilizing in-depth interviews, focus group discussions, and direct simulations of QRIS use in daily transactions. The results show that resistance to the use of QRIS is largely due to limited understanding of digital technology, low levels of trust in the security of electronic payment systems, and constraints on internet access and stability in the study area. In addition, factors such as habit, the age of business owners, and the perception of greater control when using cash also reinforce the preference for conventional transactions. However, around 60% of respondents showed an increase in understanding, confidence, and a more open attitude after receiving education on the benefits, security, and efficiency of using QRIS. These findings confirm that contextual digital financial literacy education strategies are effective.Keywords : Digital Financial Literacy, Digital Payments, Digital Transformation, MSMEs, QRIS